Optoelectronic neuromorphic thin-film transistors capable of selective attention and with ultra-low power dissipation. (August 2019) - Yu, J.J.; Liang, L.Y.; Hu, L.X.; Duan, H.X.; Wu, W.H.; Zhang, H.L.; Gao, J.H.; Zhuge, F.; Chang, T.C.; Cao, H.T.
Abstract: Compared to purely electrical neuromorphic devices, those stimulated by photon, pressure, or/and chemical signals have gained burgeoning attentions due to their real sense simulating. Herein, we demonstrate a novel optoelectronic neuromorphic device based on pn-junction-decorated oxide thin-film transistor that can response to broadband vision data ranging from ultraviolet to visible light region in a neuromorphic system. Versatile synaptic behaviors such as short-term plasticity, long-term plasticity, neural potentiation and neural depression are successfully simulated. Extraction and analysis on the density of photoexcited V O -related-defect states, activation energy for photocarrier relaxation are performed to gain deep insights into the inherent correlation between the photocarrier relaxation route and the synaptic behaviors. Owing to the gate bias control capability, 'selective amnesia and memory' behaviors can be created by applying different gate voltage pulses. Through defect state management in the channel, device structure design and operation mode selection, the proposed devices have an ultralow electrical power consumption less than 10 pW. Finally, fully-transparent visible-light-stimulated synaptic transistors have been tentatively illustrated as well, capable of sensing a blue light pulse with the intensity down to 0.3 μW/cm 2 . Graphical abstract: Image 1 Highlights: Optoelectronic synapses capable of 'selective amnesia and memory' behaviors. Versatile synaptic behaviors enabled by the ultraviolet and the whole visible light stimuli. Tunable synaptic plasticity through controlling the device structure, channel defects and operation scheme.Tunable synaptic plasticity through controlling the device structure, channel defects and operation scheme. The underlying mechanisms based on the voltage-tunable photocarrier relaxation route. Fully-transparent photonic synaptic devices with low electrical and light power consumption.